1997
DOI: 10.1080/15216549700201731
|View full text |Cite
|
Sign up to set email alerts
|

Quenching of singlet molecular oxygen by carnosine and related antioxidants. Monitoring 1270‐nm phosphorescence in aqueous media

Abstract: In order to elucidate the biochemical roles of imidazol-containing dipeptides, we have studied quenching of singlet molecular oxygen (IO2) by carnosine (13-alanyl-L-histidine), its structural components (L-histidine, imidazole, and 13alanine), and related natural free-radical scavengers -L-anserine ([3-alanyl-l-methylhistidine), ergothioneine (2-thiol-L-histidine-betaine), and taurine (2aminoethanesulfonic acid) in aqueous (D20, pD 7) solutions by using monitoring of 102-phosphorescence (1270-nm). The rate con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2004
2004
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 6 publications
0
13
0
Order By: Relevance
“…The bacterial log cell kills observed in this study are significant and similar to those observed in experimental animals, but lower than those readily achievable in vitro , even under much less stringent conditions 9 . The reasons for this have not been fully explored but could relate to sequestration of the drug by proteins and other biomolecules, release of one or more singlet oxygen quenchers by tissue (carnosine from muscle is a known quencher of singlet oxygen), depletion of oxygen by PDT in the biological environment or the effect of biological surfaces 27,28 . These factors merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…The bacterial log cell kills observed in this study are significant and similar to those observed in experimental animals, but lower than those readily achievable in vitro , even under much less stringent conditions 9 . The reasons for this have not been fully explored but could relate to sequestration of the drug by proteins and other biomolecules, release of one or more singlet oxygen quenchers by tissue (carnosine from muscle is a known quencher of singlet oxygen), depletion of oxygen by PDT in the biological environment or the effect of biological surfaces 27,28 . These factors merit further investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Boldyrev et al (1997) have suggested that the antioxidant protective effects of carnosine can relieve some of the fatigue induced effects due to its binding affinity for reactive species, such as hydroxyl radicals and ROS, therefore preventing compounded damage. Egorov et al (1997) provided further evidence for an antioxidant effect of carnosine attributing its ability to quench singlet oxygen molecules to its functional imidazole structure. Kohen et al (1988) suggests that a drop in pH hinders the scavenging abilities of histidine-related compounds, however, the high-buffering capacity of carnosine allows for a unique antioxidant ability by prolonging physiological pH values (Parkhouse et al 1985).…”
Section: Exercise-induced Oxidative Stressmentioning
confidence: 96%
“…The C max of anserine in plasma was reported to be 2.72 ± 1.08 µM at 100 min after ingesting 150 g of chicken breast. Although the biochemical function of histidine-dipeptides is still not clear, there is evidence that histidine-dipeptides could act as both a direct antioxidant by scavenging peroxyl radicals and singlet oxygen, and as an indirect antioxidant by deactivating the pro-oxidant effect of transition metal ions through a chelating mechanism [33-35]. …”
Section: Histidine-dipeptides Carnosine and Anserinementioning
confidence: 99%